2019
DOI: 10.1249/mss.0000000000002222
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Respiratory Muscle Responses to Hyperpnea or Loaded Breathing in COPD

Abstract: Introduction: To compare acute mechanical and metabolic responses of the diaphragm and rib cage inspiratory muscle during two different types of respiratory loading in patients with COPD. Methods: In 16 patients (age:65±13, 56% male, FEV1:60±6%pred, Pimax:82±5%pred) assessments of respiratory muscle electromyography (EMG), esophageal (Pes) and gastric (Pga) pressures, breathing pattern, and noninvasive assessments of systemic (VO2, cardiac output, oxygen delivery and extraction) and respiratory muscle hemodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 46 publications
5
34
1
1
Order By: Relevance
“…An increase in SM,RMS %max during hypoxic hyperpnea compared to normoxic hyperpnea has been described (Katayama et al, 2015). Although hyperpnea and ITL provide different mechanical and physiological stimuli to the respiratory muscles (Rodrigues et al, 2019), our findings show that the same pattern of increase in SM,RMS %max was present during ITL. Also in patients with chronic obstructive pulmonary disease (COPD), the SM demonstrated greater activation during constant-load ITL at 30% (Andrade et al, 2005) or 50% (Rodrigues et al, 2019) of MIP, as well as during resting hyperpnea (Rodrigues et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…An increase in SM,RMS %max during hypoxic hyperpnea compared to normoxic hyperpnea has been described (Katayama et al, 2015). Although hyperpnea and ITL provide different mechanical and physiological stimuli to the respiratory muscles (Rodrigues et al, 2019), our findings show that the same pattern of increase in SM,RMS %max was present during ITL. Also in patients with chronic obstructive pulmonary disease (COPD), the SM demonstrated greater activation during constant-load ITL at 30% (Andrade et al, 2005) or 50% (Rodrigues et al, 2019) of MIP, as well as during resting hyperpnea (Rodrigues et al, 2019).…”
Section: Discussionsupporting
confidence: 77%
“…In healthy young adults, the SM does not appear to be recruited during resting breathing or low-intensity ITL (Chiti et al, 2008;Nobre et al, 2007). However, SM,RMS %max has consistently shown to be increased when higher loads are imposed on the respiratory system (De Troyer & Boriek, 2011;Katayama et al, 2015;Rodrigues et al, 2019;Shadgan et al, 2011). An increase in SM,RMS %max during hypoxic hyperpnea compared to normoxic hyperpnea has been described (Katayama et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…IMT has been recommended in patient with inspiratory muscle weakness [ 21 ]. IMT reportedly increases ribcage and neck muscle activation, and these muscle recruitment serve as a reserve to overcome increasing demand [ 12 ]. As the inspiratory muscles might become already trained [ 22 ], IMT is not effective in patients with COPD and high MIP (inspiratory muscle function > 60 cmH 2 O) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the observations abovementioned, IMT might change a breathing pattern other than dynamic hyperinflation and subsequently affect exercise tolerance in patients with COPD. Given that IMT activates inspiratory muscles and induces deeper breathing [ 12 , 13 ], we hypothesized that the improvement of exercise tolerance might be depended on the degree of ventilatory efficiency obtained from IMT.…”
Section: Introductionmentioning
confidence: 99%
“…Two alternative interventions with the potential to acutely lower BP and improve sleep without requiring activity from the upper or lower limbs are voluntary normocapnic hyperpnea (HYP) and intermittent hypoxia (IH). HYP can be seen as a form of exercise as it involves repetitive contractions of (upper body) skeletal muscles and shows typical cardiorespiratory responses to exercise as other modalities, such as an increase in heart rate, stroke volume and mean arterial pressure ( Rodrigues et al, 2020 ). Previous research has shown that periods of HYP training, with sessions typically lasting 30 min while breathing at ∼60% of maximal voluntary ventilation, is successful in increasing the endurance of the respiratory muscles as well as whole-body exercise performance ( Illi et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%